Implementasi Pembelajaran Aswaja Melalui Bercerita/Mendongeng di MI Nurul Munim Paiton Probolinggo - M. Mahbubi; Fikri Aldo Noviantoro; Muhammad Anwari; Rifki Arif (STAIFAS-Press, 2021)
Education, which is currently full of competitive competition, makes students easy to experience stress, resulting in discrimination against moral values. The importance of moral values in education motivates students to behave well and create a balanced life. Islamic Religious Education has religious activities and also personal values to apply and get used to good behavior not only at school but also in the community. As one of the means of implementing self-reliance to achieve learning targets carried out at MI Nurul Munim is a learning method through storytelling or storytelling because these methods are very effective for student learning by imitating the character traits told by the teacher. In addition to implementing learning MI Nurul Munim also carries out extra activities such as istighosah activities as a religious means to increase devotion to Allah SWT. One of the prudential implementations implemented at MI Nurul Muim is the etiquette of kissing hands to maintain the value of politeness and etiquette to teachers, but this has problems due to health protocols to anticipate the spread of covid-19. Pendidikan yang saat ini penuh dengan persaingan yang kompetitif membuat siswa mudah mengalami stres, sehingga terjadi diskriminasi terhadap nilai-nilai moral. Pentingnya nilai moral dalam pendidikan memotivasi siswa untuk berperilaku baik dan menciptakan kehidupan yang seimbang. Pendidikan Agama Islam memiliki kegiatan keagamaan dan juga nilai-nilai pribadi untuk diterapkan dan dibiasakan berperilaku baik tidak hanya di sekolah tetapi juga di masyarakat. Sebagai salah satu sarana pelaksanaan kemandirian untuk mencapai target pembelajaran yang dilakukan di MI Nurul Munim adalah metode pembelajaran melalui storytelling atau mendongeng karena metode tersebut sangat efektif untuk pembelajaran siswa dengan meniru sifat-sifat karakter yang diceritakan oleh guru. Selain melaksanakan pembelajaran MI Nurul Munim juga melaksanakan kegiatan ekstra seperti kegiatan istighosah sebagai sarana keagamaan untuk meningkatkan ketaqwaan kepada Allah SWT. Salah satu penerapan kehati-hatian yang diterapkan di MI Nurul Muim adalah etika berciuman untuk menjaga nilai kesopanan dan tata krama kepada guru, namun hal ini terkendala karena protokol kesehatan untuk mengantisipasi penyebaran covid-19.